Medical Query Language - Morgan, Mary M. (1981)
This paper describes the Medical Query Language (MQL), a “formal” language which enables unsophisticated users, having no background in programming or computer science, to express information retrieval and analysis questions of their data bases. MQL is designed to access any MUMPS data base. Most MQL applications to date have dealt with the COmputer STored Ambulatory Record (COSTAR) data base.